Violencia de género y feminización de la pobreza en las mujeres montuvias de Ecuador (Sección Abierta) - León Muñoz, Raisa Jomaira (2022)
In this paper, the social context of Montuvian women will be analyzed to understand their sociocultural situation. Through secondary sources, the topic of gender violence in public and private spaces will be analyzed, triggering institutional violence that they suffer when they go to protective and judicial institutions that serve the victims. The elements of intersectionality that influence the justiciability of Montuvian women´s rights will be studied. This contribution will address the feminization of poverty due to inequality, resulting from being under a patriarchal dominance structure. An analysis of poverty is also presented as a global phenomenon that mainly affects Montuvian women since in this group, lack of schooling, access to work and adequate housing perpetuate their situation of social inequality. Research on gender violence in Montuvian women was carried out through case studies, the main tools being interviews to analyze the stories of women who manifest discrimination, precariousness, rurality; evidencing a complex scenario of vulnerability.